Efektifitas Penyuluhan Dengan Media Audio Visual Terhadap Pengetahuan Dan Sikap Pus Dalam Pemilihan Kontrasepsi IUD - SAFITRI, OKTARIA; Sutrinigsih, Sutriningsih (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Contraception IUD (Intra Uterine Device) or IUD is a device or object inserted into the uterus that is very effective, reversible and long-term, can be used by all women of reproductive age, with the aim of contraception or pregnancy prevention efforts in Lampung Province from the number of couples aged fertility in 2015 decreased by (5.38). The aim of this research is to determine the effectiveness of counseling using leaflet media on the knowledge and attitudes of PUS in selecting IUD contraception. The research method used in this research is quasi-experimental research with a one-gretest pretest-posttest design. The results of this research are test Marginal Homogeneity statistics obtained P-value 0.0001 < α 0.05. There are differences in the level of knowledge before and after intervention using audiovisual media in women of childbearing age. It is known that before the intervention women of childbearing age had a good level of knowledge as many as 4 respondents. Conclusion Audiovisual media is a very effective medium in increasing a person's knowledge due to its unique, creative and innovative presentation. The suggestion of this research is to further improve the use of audiovisual media in providing information so that public knowledge about health, especially family planning programs, becomes even better.